Analisis Peramalan Kebutuhan Komponen Minifix Bolt Dia di PT XYZ Menggunakan Metode Time Series - Alfan Afiyudin; Dwi S. Donoriyanto (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
PT XYZ is a company that produces furniture products that use the "Make to stock" method to meet consumer demand. In the production process, there is often a buildup of raw materials, one of which is the minifix bolt component, which causes a buildup of raw materials in the warehouse. Therefore, it is necessary to forecast raw materials to predict the amount of raw materials each period. In the forecasting process, you can use the moving average and single ex-ponential smoothing methods. From the calculation results using the POM-QM software, the MAD (Mean Absolute Deviation) value was 13,111.11, MSE (Mean Squared Error) was 261,975,300, MAPE (Mean Absolute Percent Error) was 226,303%. From the software output results, it is known that the smallest MAD, MSE, and MAPE values ​​of the three methods are the moving average method. So this method was chosen to solve problems within the company because the smaller the error that occurs, the smaller the possibility of something bad happening.